Peran Komunitas Pendidikan Non Formal Kakak Aman Indonesia dalam Pencegahan Paparan Pornografi pada Anak - Farhan, Muhamad; Maysara, Siska Resti (ALSYS, 2025)
The rapid advancement of information and communication technology has brought significant changes across various aspects of life, including how children and adolescents interact with digital media. TikTok, as one of the most popular social media platforms, offers creative features and an engaging algorithm, yet poses considerable risks to children’s social and psychological development—particularly regarding exposure to harmful content such as pornography. This study aims to examine the role of the non-formal education community Kakak Aman Indonesia in equipping children with the knowledge and skills needed to face the challenges of the digital world. Using a descriptive qualitative approach, data were collected through observation and documentation of community activities. The findings reveal that Yayasan Kakak Aman Indonesia plays an active role in preventing exposure to pornographic content through three key strategies: (1) providing digital education for children and parents about the dangers of negative online content; (2) training children in independent, healthy, and safe use of digital media; and (3) offering safe, child-friendly spaces for discussion and reporting cases of sexual violence and pornography exposure. These findings underscore the importance of non-formal educational collaboration in creating a safe digital environment that supports children's growth and development. The implication is that programs such as those conducted by Kakak Aman Indonesia can serve as effective community-based preventive intervention models in addressing the challenges of the digital era.